DETERMINANTS OF SHEEP FARM PROFITABILITY: EVIDENCE FROM SMALLHOLDER FARMS IN TEGAL REGENCY, INDONESIA - Muhammad Difa Ash-Shadiq (RADJA PUBLIKA, 2026)
This study examines the effects of feed cost, farm size, selling price, education level, farming experience, and access to credit on the profitability of sheep farming enterprises in Tegal Regency, Indonesia. A quantitative approach with an associative research design was employed using survey data collected from 40 sheep farmers selected through purposive sampling. Data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression with IBM SPSS. The findings indicate that all independent variables have positive and statistically significant effects on farm profitability (p < 0.05). Feed cost is identified as the most influential determinant (β = 0.841), followed by selling price, education level, farm size, farming experience, and access to credit. Furthermore, the simultaneous regression analysis confirms that these variables collectively have a significant effect on profitability (F = 356.970; p < 0.001). The coefficient of determination (R² = 0.685) indicates that 68.5% of the variation in farm profitability is explained by the proposed model, while the remaining 31.5% is attributable to other factors beyond the scope of this study. These findings suggest that improving sheep farm profitability requires an integrated strategy emphasizing efficient feed management, appropriate business scale, competitive selling prices, human capital development, and improved access to financial resources. The study provides practical implications for farmers, policymakers, and extension agencies in promoting sustainable and competitive smallholder sheep farming.